Work Effectiveness of Administration Employees at SMK Negeri 2 Gowa - Saleh, Sirajuddin; Ahmad, Ajeng Trisnawati; Arhas, Sitti Hardiyanti (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The quality of the school is greatly influenced by its administrative management. This study aims to determine the Work Time utilization of Administration Employees at SMK Negeri 2 Gowa. This research is a descriptive research with a qualitative approach, so that to achieve the research objectives, data collection techniques are used using observation, interview and documentation techniques. The informants in this study were 5 people. Data analysis techniques in this study are using data collection techniques, data condensation, data presentation, drawing conclusions / verification. The results showed that the time utilization of the work of administrative employees at SMK Negeri 2 Gowa was in the category of quite effective. This is evidenced by: 1) The quantity of work, the work of administrative employees has reached the set target, employees complete all work assigned according to standards and orders, the distribution of tasks and workload is carried out evenly based on their fields. 2) The quality of work, administrative employees already have knowledge and understanding related to their duties, the ability of employees and the accuracy of work results are good enough but for some employees still need to be improved. Efforts to improve the quality of employee work still need to be carried out regularly such as training and coaching. 3) Time utilization, administrative employees work based on the specified working time and complete their work on time, but some administrative employees have not maximized their work time and still often postpone work.